(untitled) (Research, Society and Development, 2024)
Introduction: This article aims to discuss the importance of breastfeeding and the role of nurses in the Family Health Strategy (FHS) in guiding families through this process. Methodology: A literature review was conducted, selecting 20 articles based on inclusion and exclusion criteria. 2: Additionally, it highlights the significant role of nurses in educating pregnant women and postpartum mothers about breastfeeding. Health Sciences Descriptors (DeCS) were used: Nurse, Breastfeeding, Pregnant women, Guidance, using the boolean operator AND. Conclusion: It is crucial for nurses to continue to encourage these women through health promotion efforts, aiming to reduce infant morbidity and mortality and early weaning, particularly in cases where preventable factors exist (such as mastitis, diarrheal diseases, and malnutrition).